Violation of the Engineer's Code of Ethics in Recruiting Welder Qualifications Project PLTM Parmonangan - Rijal S. Simanungkalit; Eka Daryanto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The Engineering Profession carries high moral and legal responsibilities, and is obligated to adhere to the Indonesian Engineers Code of Ethics (KEII) to prioritize public safety. This mini-research examines the dilemma of Engineer integrity during the qualification process of welders for high-pressure pipeline (penstock) installations at the Parmonangan Mini-hydro Power Plant (PLTM) Project. Pressure from project management regarding cost and schedule potentially drives ethical compromises that endanger construction quality and operational safety. This research uses a Descriptive-Analytical Qualitative Case Study approach. Data was collected through a triangulation of findings from interviews with the Project Engineer, analysis of qualification documents, and field observation (Non-Destructive Testing/NDT results) at the Parmonangan PLTM Project. A critical technical gap was found: the project mandated 5G/6G welder qualification (ASME/AWS) for the penstock, yet the Project Engineer accepted welders with a lower 3G qualification, driven by cost and schedule pressures. This practice resulted in a high incidence of weld defects (e.g., porosity and undercut) requiring repair. This compromise was proven to violate fundamental points of the KEII: Mandate 1 (Public Safety): The decision to accept non-competent welders increased the risk of penstock failure, threatening public safety. Mandate 3 (Competence): The Engineer approved work that was technically unjustifiable according to standards. Mandate 6 (Professional Integrity): The Engineer failed to avoid a conflict of interest between ethical obligations and commercial interests. The practice of accepting welders with inadequate qualifications at the Parmonangan PLTM Project constitutes a fundamental violation of the KEII caused by business pressures. This not only diminishes construction quality but also potentially leads to long-term technical consequences, namely reduced integrity and service life of the facility. It is necessary for the Project Owner to affirm quality and safety as non-negotiable criteria. Furthermore, the Indonesian Engineers Association (PII) must strengthen mechanisms for professional protection for Engineers who reject management policies that violate the code of ethics and technical standards.